Hydrogen peroxide modulates synaptic transmission in ventral horn neurons of the rat spinal cord. (7th December 2015) - Ohashi, Masayuki; Hirano, Toru; Watanabe, Kei; Katsumi, Keiichi; Ohashi, Nobuko; Baba, Hiroshi; Endo, Naoto; Kohno, Tatsuro
Abstract : Key points: Excessive production of reactive oxygen species (ROS) is implicated in many central nervous system disorders; however, the physiological role of ROS in spinal ventral horn (VH) neurons remains poorly understood. We investigated how pathological levels of H2 O2, an abundant ROS, regulate synaptic transmission in VH neurons of rats using a whole‐cell patch clamp approach. H2 O2 increased the release of glutamate and GABA from presynaptic terminals. The increase in glutamate release involved N‐type voltage‐gated calcium channels (VGCCs), ryanodine receptors (RyRs), and inositol trisphosphate receptors (IP3 Rs); the increase in GABA release, which inhibited glutamatergic transmission, involved IP3 R. Inhibiting N‐type VGCCs and RyRs attenuates excitotoxicity resulting from increased glutamatergic activity while preserving the neuroprotective effects of GABA, and may represent a novel strategy for treating H2 O2 ‐induced motor neuron disorders resulting from trauma or ischaemia–reperfusion injury. Abstract: Excessive production of reactive oxygen species (ROS) is a critical component of the cellular and molecular pathophysiology of many central nervous system (CNS) disorders, including trauma, ischaemia–reperfusion injury, and neurodegenerative diseases. Hydrogen peroxide (H2 O2 ), an abundant ROS, modulates synaptic transmission and contributes to neuronal damage in the CNS; however, the pathophysiological role of H2 O2 in spinal cord ventral horn (VH) neurons remains poorly understood, despite reports that these neurons are highly vulnerable to oxidative stress and ischaemia. This was investigated in the present study using a whole‐cell patch clamp approach in rats. We found that exogenous application of H2 O2 increased the release of glutamate from excitatory presynaptic terminals and γ‐aminobutyric acid (GABA) from inhibitory presynaptic terminals. The increase of glutamate release was induced in part by an increase in Ca 2+ influx through N‐type voltage‐gated calcium channels (VGCCs) as well as by ryanodine receptor (RyR)‐ and inositol trisphosphate receptor‐mediated Ca 2+ release from the endoplasmic reticulum (ER). In inhibitory presynaptic neurons, increased IP3 R‐mediated Ca 2+ release from the ER increased GABAergic transmission, which served to rescue VH neurons from excessive release of glutamate from presynaptic terminals. These findings indicate that inhibiting N‐type VGCCs or RyRs may attenuate excitotoxicity resulting from increased glutamatergic activity while preserving the neuroprotective effects of GABA, and may therefore represent a novel and targeted strategy for preventing and treating H2 O2 ‐induced motor neuron disorders. Key points: Excessive production of reactive oxygen species (ROS) is implicated in many central nervous system disorders; however, the physiological role of ROS in spinal ventral horn (VH) neurons remains poorly understood. We investigated how pathological levels of H2 O2, an abundant ROS, regulate synaptic transmission in VH neurons of rats using a whole‐cell patch clamp approach. H2 O2 increased the release of glutamate and GABA from presynaptic terminals. The increase in glutamate release involved N‐type voltage‐gated calcium channels (VGCCs), ryanodine receptors (RyRs), and inositol trisphosphate receptors (IP3 Rs); the increase in GABA release, which inhibited glutamatergic transmission, involved IP3 R. Inhibiting N‐type VGCCs and RyRs attenuates excitotoxicity resulting from increased glutamatergic activity while preserving the neuroprotective effects of GABA, and may represent a novel strategy for treating H2 O2 ‐induced motor neuron disorders resulting from trauma or ischaemia–reperfusion injury.